Systematic review and meta-analysis of the efficacy of gabapentin in chronic female pelvic pain without another diagnosisAJOG Global Reports at a Glance - Greg Marchand, MD, FACS, FICS, FACOG; Ahmed Taher Masoud, MD; Malini Govindan, MD, FACOG; Kelly Ware, MS; Alexa King, BS; Stacy Ruther, BS; Giovanna Brazil, BS; Kaitlynne Cieminski, BS; Nicolas Calteux, BS; Catherine Coriell, BS; Hollie Ulibarri, BS; Julia Parise, BS; et al. (Elsevier, 2022)
Background: While widely used for the treatment of chronic pelvic pain, limited data exists on efficacy of gabapentin, especially in the subgroup of women suffering from chronic pelvic pain without a known diagnosis, such as endometriosis. Objective: This study aimed to assess the efficacy of gabapentin when administered to women with chronic pelvic pain without another diagnosis. Study Design: We performed a Systematic Review and Meta Analysis including all controlled clinical trials addressing the use of gabapentin for the treatment of chronic pelvic pain without another diagnosis. We searched PubMed, Scopus, Web of Science, ClinicalTrials.Gov, MEDLINE, and The Cochrane Library from inception of each database to April 30, 2021. We included all the studies that fulfilled the following criteria: (1) population: women suffering from chronic pelvic pain without another identified diagnosis (such as endometriosis); (2) intervention: gabapentin (regardless of the dosage); (3) comparator:placebo; (4) outcomes: pain score (visual analog scale) after 3 months and pain score (visual analog scale) after 6 months as primary outcomes; and (5) study design: we only included randomized or controlled clinical trials. Our exclusion criteria included (1) uncontrolled clinical trials, (2) studies that did not report data or measures for any of our selected outcomes, (3) studies that included patients with surgically or clinically diagnosed endometriosis, or (4) studies with no full-text manuscript available. Risk of bias assessment was performed using the Cochrane risk of bias tool. We analyzed dichotomous outcomes as percentages and totals, whereas continuous outcomes were analyzed using mean difference, standard deviations, and relative 95% confidence intervals using the inverse variance method. Results: We included 4 placebo-controlled randomized controlled trials. Analysis was hindered because half of the studies (n=2) used the visual analog scale pain score and the other half (n=2) used the numerical rating scale. The analysis showed that when compared with the placebo, gabapentin significantly lowered the visual analog scale pain score at 3 months (mean difference, 0.79; 1.23 to 0.35; P=.005) and 6 months (mean difference, 1.68; 2.30 to 1.05; P=.001) and the numerical rating scale pain score at 3 months (mean difference, 0.20; 0.25 to 0.15; P=.001). However, in terms of the numerical rating scale pain score after 6 months, the 2 groups showed no significant difference (mean difference, 0.27; 0.80 to 0.26; P=.32). CONCLUSION: Gabapentin may hold benefit for the management of chronic pelvic pain, with significant improvement in pain seen in both scales at 3 months when compared with the placebo, but only in the visual analog scale group at 6 months of usage. Secondary to the differences in the nature of the 2 scales, a further weighted combined analysis was not possible.